ANALISIS KELAYAKAN DAN KERAGAAN PEMASARAN USAHA TERNAK AYAM RAS PEDAGING DI KOTA SINGKAWANG (The Feasibility Analysis and Performance of Business Marketing Livestock Chicken in Singkawang) - ADISUCIPTO, ADISUCIPTO; SUDRAJAT, JAJAT; NURLIZA, NURLIZA (Jurnal Social Economic of Agriculture, 2016)
Results of research conducted in Singkawang in livestock farming of broiler patterns and Partnership Informal self with the business scale of 1,500 to 5,000 chickens per period. Breeders pattern of self-marketing results directly to the consumer the highest price of Rp. 23,800, - and the lowest Rp. 22.200, - with a mean weight of 1.46 kg per cow a chicken and informal partnership schemes carried out by a partnership the marketing of the highest price of Rp. 18,800 and the lowest is Rp. 18.000, - with an average weight of 1.78 kg per cow chicken. Recapitulation of the average calculation feasibility criteria breeders independently pattern obtained NVP is Rp. 2,537,399.33, Net B / C ratio is 17.73 and the IRR is 13.89% and the payback period is 3.31, a business worth continuing. Breeders pattern generating informal partnership NVP Rp. -13,573,023.9, -. Net B / C ratio is -8.44 and the IRR is 10.94% and the payback period is 4.35, it is not feasible to continue. Followed by calculation assuming operating costs and revenue rose by 18%. Breeders pattern independently obtain NPV value of Rp. 52,298,383.8,-. Net B / C Ratio is 3.85, which is 12.5% IRR, payback period 4.68 was obtained. Breeders informal partnership scheme obtain NPV value of Rp. 631 387, - Net B / C ratio is 1.02. IRR obtained is 13.0%, payback period of 6.09 is obtained, it deserves to be continued. A sensitivity analysis chicken feed decreased by 5% farmers obtain independent patterns NPV Rp. 17,224,284.29. Net B / C ratio of 6.99. IRR of 26.0% was obtained. Payback Period of 2.6, the effort worth continuing. Breeders informal partnership scheme to obtain NPV of Rp. -2,800,267. Net B / C Ratio is equal to -2.06. IRR obtained by 11.35% and PP by 3, 6, was not worth continuing.Keywords: Analysis, Feasibility and Marketing